Bio-mulches on moisture and biological properties of soils under maize-legume sequence - Joy, K D; Binoy, K S; Rajib, D; Ashim, D; Ardhendu, C; Pramod, D (Plant Science Today, 2025)
To find out the best combination of cropping sequence and level of mulching for growing of Rabi legumes in maize-legume sequence. The present field experiment was conducted during 2017-18 and 2018-19 at the Agricultural Farm of Institute of Agriculture, Visva Bharati, located in Sriniketan, West Bengal using split plot design (SPD) with three main plots as cropping system (CS1: maize-chickpea; CS2: maizelentil; CS3: maize-lathyrus) and five sub-plot as mulching (M0: No mulch (residue removal); M1: In-situ maize stalk mulch (MSM); M2: MSM + water hyacinth (5 t ha-1); M3: MSM + paddy straw (5 t ha-1); M4: MSM + paddy straw (2.5 t ha-1) + water hyacinth (2.5 t ha-1)) and the experiments were replicated four times. In the present study, we have formulated locally available bio-mulches for the efficient moisture conservation and improving soil microbial conditions for growing Rabi pulses (chickpea, lentil, lathyrus) after Kharif maize under zero tillage. Among the bio-mulches, highest soil microbial biomass carbon (SMBC) (196.87 and 200.59 μg g-1 soil) and dehydrogenase activity (DHA) (25.32 and 26.70 μg TPF hr-1 g-1 ) were recorded at 0-15 cm soil under MSM + paddy straw (5 t ha-1) mulch (M3) and in cropping sequence, highest water use efficiency was showed by maize-lathyrus (CS3) (1.33 and 1.37 kg ha-1 mm-1) for 2017-18 and 2018-19 respectively under MSM + paddy straw (5 t ha-1) mulch (M3). Bio-mulches conserve soil moisture and improved the soil biological properties and gave higher water productivity and water use efficiency.